Gender and tourism : challenges and entrepreneurial opportunities - Valeri, Marco; Katsoni, Vicky (Emerald Publishing Limited, 2021)
Gender and Tourism: Challenges and Entrepreneurial Opportunities adopts a multi-disciplinary approach, building on a historically informed, future-focused research agenda that accounts for the needs and concerns of contemporary policy makers and practitioners in the tourism field. The collection is structured in two parts, with the first part collecting chapters that analyze the key factors of female entrepreneurship in the tourism sector, the participation of women at leading, decision making positions worldwide, the potential of female business development in both global and local terms and the main inhibitors for their under representation in top managerial key positions. The second part includes chapters that investigate, through significant case studies, which is the most appropriate governance and management model to be implemented in the context of gender and tourism. Gender and Tourism is the result of reflections on researches of different nationalities and provides a comprehensive collection of new insights for traditional paradigms, approaches and methods, as well as exploring more recent developments in research methodology in the context of gender and tourism studies.
Includes index.
Keywords: Women in tourism.; elektronické knihy; electronic books